ANALYSIS OF PROPERTIES OF CONCRETE USING DRIED BANANA PEEL POWDER AS ADMIXTURE - Gadgihalli, Vishal; Meena; Shankar, Sindhu; Havanje Dinakar, Raghavendra Prasad (International Journal of Research -GRANTHAALAYAH, 2017)
Ingredients other than cement, water& aggregates that import a specific quality to either plastic(fresh)mix or the hardened concrete (ASTMC 496) is called concrete admixture. In this paper analysis of properties of concrete using banana peel as admixture is studied and verified the strength of concrete and temperature emitted due to chemical reaction to the normal Portland cement. As banana’s peel is rich in natural fiber and it is well known source of potassium. The flexural strength of concrete by using banana peel powder as admixture has increased, but considerable lesser compressive strength has increased. The percentage of transmission temperature and reduction time of temperature has decreased; hence it is clear that the exothermal reaction in concrete has been reduced by using dried banana peel powder as admixture.